Le grand mal de l'époque: Tocqueville on French Political Corruption. Issue 1 (2nd January 2016) - Selinger, William
SUMMARY: During the years he was involved in French parliamentary politics, Alexis de Tocqueville was obsessed with the issue of political corruption. This article presents the first sustained analysis of Tocqueville's speeches and writings on French corruption. It examines Tocqueville's initial encounter with corruption during his run for parliamentary office, his sophisticated account of the sources of corruption, and his strategies for reforming French politics. The article contends that taking seriously Tocqueville's struggle against corruption has the effect of complicating several conventional interpretations of his thought. In his speeches and writings on corruption Tocqueville shows himself remarkably willing to compromise with, even to work with, centralisation. And he argues that in a nation like France which lacks substantial local self-government, a vibrant parliamentary politics could be an effective means for promoting energetic civic participation.